Day 2 Wed, October 30, 2019 2019
DOI: 10.4043/29909-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rock Aging Time on the Initial Wettability of Minerals and Analogue Rocks Using Pre-Salt Fluids Under Reservoir Conditions

Abstract: Wettability is an important property in reservoir characterization. For the heterogeneous carbonate reservoirs in the Brazilian Pre-Salt, parameters that represent wettability are needed to obtain improved reservoir models. In this work, we applied contact angle measurements to analyze rock-fluid interactions between synthetic brine, crude oil from a Pre-Salt field and rocks and minerals with similar characteristics to the Pre-Salt formations. We studied the effects of aging time on different solid substrates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In addition, temperature, pressure, and the aging time of the reservoir's rocks with crude oil also have a significant influence on the EOR additive performance. [59][60][61] Although the literature shows that low-salinity systems are capable of decreasing the residual oil content, the flooding with just brine in the solution presented a poor performance, demonstrating the need for the implementation of an EOR process. 44 The chitosan derivatives were able to satisfactorily increase the residual oil recovery factor in the porous medium experiment.…”
Section: Oil Recovery Test In An Unconsolidated Porous Mediummentioning
confidence: 99%
“…In addition, temperature, pressure, and the aging time of the reservoir's rocks with crude oil also have a significant influence on the EOR additive performance. [59][60][61] Although the literature shows that low-salinity systems are capable of decreasing the residual oil content, the flooding with just brine in the solution presented a poor performance, demonstrating the need for the implementation of an EOR process. 44 The chitosan derivatives were able to satisfactorily increase the residual oil recovery factor in the porous medium experiment.…”
Section: Oil Recovery Test In An Unconsolidated Porous Mediummentioning
confidence: 99%
“…It is worth mentioning that flooding tests in an unconsolidated porous medium often show higher recovery factors than those from reservoir flooding since the pore size and permeability in the unconsolidated medium are significantly higher. 48,49 Additionally, temperature, pressure, and the aging time of the reservoir's rocks with crude oil also have a significant influence on nanofluid performance. 48,49 Nanofluid Stability and Efficiency in a High-Saline Medium.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…48,49 Additionally, temperature, pressure, and the aging time of the reservoir's rocks with crude oil also have a significant influence on nanofluid performance. 48,49 Nanofluid Stability and Efficiency in a High-Saline Medium. Most of the oil reservoirs recently discovered in Brazil are formed by carbonate rocks and are located below a salt layer, in the presalt region.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similar to Alnoush et al, they reported that contact angle decreases with increasing surface roughness in both high and low salinity brines, where the surface roughness impacted the contact angle in a subtler manner in the low salinity brine. Other important aspects to be considered are preconditioning of the solid surface [24,25] and ion interaction specifically with mineral surfaces [26]. Additionally, the drop size dependance of the contact angle needs to be considered.…”
Section: Introductionmentioning
confidence: 99%